PERANAN EVENT F1H2O POWER BOAT DALAM MENINGKATKAN HUNIAN HOTEL DAN HOMESTAY DI BALIGE, KABUPATEN TOBA - Bantors Sihombing (Jurnal Ilmiah Akomodasi Agung, 2023)
Toba Regency is one of the areas that has a very large tourism potential. Located on the edge of Lake Toba, Toba Regency offers stunning natural beauty and rich culture. To increase the number of tourists who come to this area, the local government often holds various tourism events. One of the tourism events held in Toba Regency is the International Event F1 H2O Super Boat. This event is a speedboat racing championship that is participated by the best racers from all over the world. This championship is very popular and attended by thousands of speedboat racing fans from all over the world. That is why the writer is interested in conducting a research entitled "The Role of F1H2O Power Boat Event in Increasing Hotel and Homestay Occupancy in Balige, Toba Regency". This research uses a qualitative approach with data collection done by literature study. The conclusion of this research is, the International Event F1 H2O Super Boat showcases high-speed boat racing on Lake Toba. This event aims to introduce Lake Toba as one of the leading tourist destinations in Indonesia and attract the interest of foreign and domestic tourists to visit the area. The economy of the surrounding community increases, especially in terms of increasing hotel and homestay occupancy in Balige Toba Regency. The International Event F1 H2O Super Boat has a positive economic impact on the surrounding community, especially in terms of increasing hotel and homestay occupancy in Balige Toba Regency, which is the main location for holding the event. The role of the Toba Regency Government in promoting this event is to coordinate with related parties, such as the Ministry of Tourism and Creative Economy, Regional Tourism Office, hotel and other accommodation entrepreneurs, and the local community. The Toba Regency Government is also responsible for providing the infrastructure and facilities needed to support the smoothness and success of this event, such as roads, transportation, electricity, clean water, security, and others